Avaliação da seca e de suas características sobre o Estado da Paraíba utilizando dados TRMM e de pluviômetros (1998–2017) - Brasil Neto, Reginaldo Moura (2020)
Drought is a natural phenomenon originated from the absence of precipitation over a certain period that is capable of causing damage to the development of different activities in society. To analyze these phenomena, rainfall estimates from remote sensing satellites have appeared as a viable alternative to monitor droughts in the most remote and complex areas of the world. In this sense, this work aims to evaluate the spatio-temporal behavior of droughts at multiple time scales and their characteristics on the state of Paraíba, based on the Standardized Precipitation Index (SPI), using data from rainfall stations and satellite precipitation estimates TRMM (Tropical Rainfall Measuring Mission) (1998–2017). For that, monthly data from 78 pluviometric stations and 187 TRMM grids were used and analyzes of specific droughts and mesoregions were developed in eight time scales. The statistical accuracy of the satellite was assessed from 11 metrics and the drought events were characterized in terms of duration, severity, intensity, frequency and percentage of affected area. In addition, trend analyzes were performed based on Mann-Kendall and Sen's non-parametric tests and hierarchical cluster analyzes to zonate the state in different homogeneous zones. Finally, a composite geospatial index that measures the risk of drought action at various time scales based on drought characteristics, the NIDS-Trend, was proposed. The results indicate that in the mesoregions close to the coast the satellite is less accurate in capturing the pattern of droughts, and that the results of medium-term droughts are the most expressive among the other time scales. On the other hand, more short-term drought events tend to occur and these are less long-lasting and severe than when evaluating long-term droughts, although it was not possible to identify relevant changes regarding the average intensity of the events. Regarding the trend analysis, it was noticed that the larger the time scale, the more expressive and significant the slopes of the trend lines were, and moreover, there are indications that drought events tend to be drier, longer and more severe in much of the state. The zoning regarding the pattern of droughts indicates that there is a strong tendency to divide the state into two large regions, one formed by Mata Paraibana and Agreste and another by Sertão and Borborema. As for the NIDSTrend, it was noticed that the values of short-term droughts were higher, while the risk to the action of droughts was lower for long-term droughts. Finally, it is concluded that the TRMM estimates are a useful source of data in the process of characterizing droughts over the state of Paraíba and that studies of this type should be carried out to monitor these phenomena more precisely.